I think, yes and it may be proved by the same way as for $a=2$. We note that
$$
C:=\sum_{k=0}^{2n}(-1)^k\binom{2n}k^{2a}=\left[x_1^{2n}\ldots x_{2a}^{2n}\right]
(x_1-x_2)^{2n}(x_2-x_3)^{2n}\ldots (x_{2a-1}-x_{2a})^{2a}(x_{2a}+x_1)^{2n}\\=
\left[x_1^{2n}\ldots x_{2a}^{2n}\right]F(x_1,\ldots,x_{2a}),
$$
where $$F(x_1,\ldots,x_{2a})=\prod_{j=-(n-1)}^n(x_1-x_2-j)(x_3-x_2-j)(x_3-x_4-j)\ldots(x_{2a-1}-x_{2a}-j)(x_{2a}+x_1-2n-j).$$
We denote $A=\{0,1,\ldots,2n\}$ and express the above coefficient via the values of $F$ on $A\times A\times \ldots \times A$ applying the Combinatorial Nullstellensatz formula. It is not hard to see (pretty analogous to $a=2$ case which was considered in details in my answer to the previous question) that if $F(x_1,\ldots,x_{2a})\ne 0$ for $x_i\in A$ then we must have $x_1=x_{2a-1}=0$, $x_{2a}=n$. Then $F(x_1,\ldots,x_{2n})$ is divisible by $((2n)!)^{2a}$ and the denominator in the CN formula equals $(-1)^{\sum x_i}\prod_{i=1}^{2a}x_i!(2n-x_i)!=((2n)!)^2 (n!)^2(-1)^{n+\sum_{i=2}^{2a-1}x_i}\prod_{i=2}^{2a-1}x_i!(2n-x_i)!$. It is immediately seen that $C$ is divisible by ${2n\choose n}$ (that already implies that $\hat{S}(2a,n)$ is divisible by $C_n$, as was earlier proved by Calkin by a different argument, see Vlad's reference). When $n=2^m-1$, using the fact that the product of $2n$ consecutive integers like $\prod_{j=-(n-1)}^n(x_1-x_2-j)$ is divisible by $2\cdot (2n)!$ unless $x_1-x_2\in \{n,n+1\}$ (again, see the explanation in the previous answer) and that $(2n)!/(x_i!(2n-x_i)!)$ is even when $x_i$ is odd, we see that the unique odd summand in our sum corresponds to $x_1=x_3=\ldots=x_{2a-3}=0$, $x_2=x_4=\ldots=x_{2a-2}=n+1$.